Cloning and expression of equine influenza virus nonstructural gene in prokaryotic system - Abdulhadi, Abdulrahman Dahham; Fateh Mohamed, Bashir Ahmad; Omar, Abdul Rahman; Bejo, Mohd Hair (2012)
Equine influenza virus (EIV) is a highly contagious and widely distributed viral respiratory disease of equiadae caused by type A influenza virus from the family Orthomyxovirus. Rapid diagnoses of affected horses are the front line of defence against outbreaks and an important step for epidemiological investigation. The objective of the present study was to clone, express, and purify the non-structural (NS1) protein of EIV subtype (H3N8). To obtain and develop an effective diagnostic method for equine influenza virus, the NS1 gene of H3N8 subtype was amplified by reverse transcriptase polymerase chain reaction (RT-PCR). Products were cloned into pCR2.0 using the TOPOTM TA cloning vector and subsequently sub-cloned into a prokaryotic expression vector, pRSET B. Recombinant plasmid designated as pRSET B-NS1 gene was confirmed by PCR colony screening, restriction enzyme digestion and nucleotide sequence analysis. The results showed that the recombinant NS1 was expressed in the E. coli strain BL21 (DE3)plysS after induction with IPTG. The 6x His-tagged recombinant fusion proteins were purified using the ProBondTM purification system and the expressed protein was identified by SDS-PAGE and western-blotting. A recombinant protein of approximately 13 kDa was produced.